Improving the Yield and Quality of Daptomycin in Streptomyces roseosporus by Multilevel Metabolic Engineering - Lyu, Zhong-Yuan; Bu, Qing-Ting; Fang, Jiao-Le; Zhu, Chen-Yang; Xu, Wei-Feng; Ma, Lie; Gao, Wen-Li; Chen, Xin-Ai; Li, Yong-Quan (Frontiers in Microbiology, 2022)
Daptomycin is a cyclic lipopeptide antibiotic with significant antibacterial action against antibiotic-resistant gram-positive bacteria. Despite numerous attempts to enhance daptomycin yield throughout the years, the production remains unsatisfactory. This work reports the application of multi-level metabolic engineering strategies in Streptomyces roseosporus to reconstruct a high-quality daptomycin overproducing strain L2797-VHb, including precursor engineering (i.e. refactoring kynurenine pathway), regulatory pathway reconstruction (i.e. knocking out negative regulatory genes arpA and phaR), byproduct engineering (i.e. removing pigment), multi-copy biosynthetic gene cluster (BGC), and fermentation process engineering (i.e. enhancing O2 supply). The daptomycin titer of L2797-VHb arrived at 113 mg/L with 565% higher comparing the starting strain L2790 (17 mg/L) in shake flasks and was further increased to 786 mg/L in 15L fermenter. This multi-level metabolic engineering method not only effectively increases daptomycin production, but can also be applied to enhance antibiotic production in other industrial strains.